A novel checker-patterned AlN MEMS resonator as gravimetric sensor - Lee, Man I. (2013)
This paper presents the design and experimental verification of a new class of piezoelectric aluminum nitride (AlN) resonator with checker-patterned electrode architecture for mass sensing applications. The mass sensitivity of the developed sensor is analytically derived and confirmed with FEM simulations and experimental results. The results show that a 773 MHz resonator has mass sensitivity of 175.42 μm2/ng and detection limit of 18.7 ng/cm2. The developed sensor has an obtained mass sensitivity of 2–3 times higher than that of state-of-the-art mass sensors and provides high potential for developed piezoelectric transducers for mass sensing applications.